The Sub-Saharan African Debt Problem : An Update - Greene, Joshua (IMF Working Papers; Working Paper, 1992)
This paper provides updated information on the external debt problem of sub-Saharan Africa. Between 1980 and 1990 the region's external debt more than tripled, to USD 171 billion, while debt service payments and rescheduling rose by more than 150 percent to USD 20 billion. In addition, the region continues to qualify as severely debt-distressed. During the last few years the region has benefitted from several new debt initiatives, including a substantial increase in debt cancellation by bilateral creditors and the general application of Toronto terms for debt rescheduling. There are also proposals for further debt assistance, including more liberal rescheduling terms, broader debt forgiveness, and consolidating debt relief and aid generation activities.